Management options for construction and demolition wastes from residential recuperation - Santos, Maria Teresa (2017)
Nowadays, the construction, remodelling and demolition operations can cause serious environment impacts. These activities produce materials defined as construction and demolition wastes (CDW). The CDW generated in Europe represents around 25-30 % of total waste. In EU 28 CDW production is about 821,160,000 t, but there is a significant difference among the European countries, mainly because of the variation of construction and demolition activity. In 2011, the total production of CDW in Portugal was around 930,000 t, but regional production is not homogeneous. The substantial inert fraction from the CDW makes them suitable for reuse. The present study aims to quantify and characterize CDW from residential recuperation of small constructions in Portugal and then propose mitigating measures to improve CDW management. The results obtained by bibliographic research revealed that the construction and demolition activity has decreased significantly in the last years and consequently CDW production. In addition, it was observed a big number of entities were involved in CDW management. Therefore, it was necessary to select a specific area from Portugal (Setubal region) which has thirteen City Halls. The surveys had scarce response. This can be explained by the lack of obligation of enterprises with less than ten employees to register CDW production and because in some regions the CDW are mixed with municipal solid waste. Most of the CDW collected from Setubal region was disposed in landfill. In order to reduce CDW production it is necessary to promote and make available recycled materials for small works at low cost.